2022
DOI: 10.48550/arxiv.2205.14777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraints on the Galactic Centre environment from Gaia hypervelocity stars II: The evolved population

Fraser A. Evans,
Tommaso Marchetti,
Elena Maria Rossi

Abstract: A dynamical encounter between a stellar binary and Sgr A* in the Galactic Centre (GC) can tidally separate the binary and eject one member with a velocity beyond the escape speed of the Milky Way. These hypervelocity stars (HVSs) can offer insight into the stellar population in the inner parsecs of the Milky Way. In a previous work, our simulations showed that the lack of main sequence HVS candidates in current data releases from the Gaia space mission with precise astrometry and measured radial velocities pla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 150 publications
0
3
0
Order By: Relevance
“…Finally, we note that Evans et al (2022a) show that including the positive detection of S5-HVS1 shifts the contours in 𝜂 and 𝜅 towards the right in Fig. 3.…”
Section: Constraints On the Galactic Centre Populationmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, we note that Evans et al (2022a) show that including the positive detection of S5-HVS1 shifts the contours in 𝜂 and 𝜅 towards the right in Fig. 3.…”
Section: Constraints On the Galactic Centre Populationmentioning
confidence: 61%
“…Specifically, Evans et al (2022b,a), assuming the Hills mechanism, showed that the population of HVSs predicted to be included in the Gaia radial velocity catalogue(s) strongly depends on the HVS ejection rate 𝜂 and on the slope 𝜅 of the initial mass function for the primary star in GC binaries, 𝑑𝑁/𝑑𝑚 ∝ 𝑚 𝜅 . The absence of HVSs with radial velocities and precise parallaxes in Gaia DR2 and EDR3 (see Marchetti et al 2019;Marchetti 2021), together with the detection of S5-HVS1 in the S 5 survey (Li et al 2019;Koposov et al 2020), constrains 𝜂 ∼ 10 −4 yr −1 (Evans et al 2022a) for a topheavy mass function in the GC (Lu et al 2013). The two parameters are strongly degenerate, with 𝜂 ∼ 10 −3 yr −1 being preferred for a canonical Salpeter (1955) mass function.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation